Synthesis, Characterization and Thermal Decomposition Kinetics of Some Azo Dye Complexes of Chromium(III) - Rawther, Sherif; Mohanan, K. (Asian Journal of Chemistry, 2010)
Chromium(III) complexes of 2,3-dimethyl-1-phenyl-4-(2-hydroxy- naphthylazo)-5-pyrazolone; 2,3-dimethyl-1-phenyl-4-(2,4-dihydroxy- phenylazo)-5-pyrazolone and 2,3-dimethyl-1-phenyl-4-(2- hydroxy-5-methylphenylazo)-5-pyrazolone have been synthesised and characterised on the basis of elemental analysis, molar conductance, magnetic susceptibility measurements, infrared and electronic spectral studies. Thermal decomposition kinetics of these complexes in nitrogen atmosphere was investigated by TG and DTG techniques. Kinetic parameters such as activation energy E, pre-exponential factor A and entropy of activation ΔS were calculated.